J.K. Lasser's small business taxes 2022 : your complete guide to a better bottom line - Weltman, Barbara, 1950- (J.K. Lasser series., 2021)
A complete guide to taxes for small businesses, brought to you by the leading name in taxes The over 30 million small businesses in America are the essential backbone of the American marketplace. J.K. Lasser's Small Business Taxes 2022: Your Complete Guide to a Better Bottom Line helps owners save as much as possible on taxes. If you own a small business, this comprehensive guide provides a pathway to quickly determine your tax liability and what kind of tax relief is available to you, down to the nitty gritty--even going so far as to show where to claim deductions on the IRS forms. Barbara Weltman brings her expertise to this topic, as a nationally recognized specialist in taxation for small businesses. Filled with tax facts and planning strategies, this guidebook is the ideal tool to help small business owners make business decisions on a tax-advantaged basis. Small Business Taxes 2022 also provides readers with: A complete listing of the available business expense deductions and tax credits, plus what's needed to qualify for them The most up-to-date information on current tax law and procedures, including information on the American Rescue Plan Act (ARPA) and the Consolidated Appropriations Act, 2021 (CAA) A heads up on changes ahead to optimize tax planning Sample forms and checklists to help you get organized and prepare you to submit the most complete and proper filing Small Business Taxes 2022 uses concise and plain English to help provide small business owners and their advisers a detailed overview on the tax rules they need to know.